2022
DOI: 10.1101/2022.02.16.480705
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Random Forest Classifier Uses Antibody Responses to Plasmodium Antigens to Reveal Candidate Biomarkers of the Intensity and Timing of Past Exposure to Plasmodium falciparum

Abstract: Important goals of malaria surveillance efforts include accurately quantifying the burden of malaria over time, which can be useful to target and evaluate interventions. The majority of malaria surveillance methods capture active or recent infections which poses several challenges to achieving malaria surveillance goals. In high transmission settings, asymptomatic infections are common and therefore accurate measurement of malaria burden often demands active surveillance; in low transmission regions where inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Further investigation of the squared error loss ranks for antigens measured by the malaria arrays used in Kobayashi et al 25 revealed potential novel biomarkers of the timing and intensity of past malaria exposure in adult populations. 31 In spite of the differences in manufacturing and features of the arrays used in the two datasets, our model fits quite well to both, suggesting the potential for it to be effective across multiple protein microarray studies. However, the two published studies represent a fairly narrow sample of the currently available protein microarrays, and the amount of between-array variability present is dependent, at least in part, on the manufacturing process.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Further investigation of the squared error loss ranks for antigens measured by the malaria arrays used in Kobayashi et al 25 revealed potential novel biomarkers of the timing and intensity of past malaria exposure in adult populations. 31 In spite of the differences in manufacturing and features of the arrays used in the two datasets, our model fits quite well to both, suggesting the potential for it to be effective across multiple protein microarray studies. However, the two published studies represent a fairly narrow sample of the currently available protein microarrays, and the amount of between-array variability present is dependent, at least in part, on the manufacturing process.…”
Section: Discussionmentioning
confidence: 74%
“…Finally, we showed how the ranks of proteins and therefore subsequent analysis can be impacted by the choices of both preprocessing and ranking methods. Further investigation of the squared error loss ranks for antigens measured by the malaria arrays used in Kobayashi et al 25 revealed potential novel biomarkers of the timing and intensity of past malaria exposure in adult populations 31 …”
Section: Discussionmentioning
confidence: 99%
“…In both cases, however, the use of the full posterior distributions to produce optimal ranks under different loss functions substantially changes the ordering and composition of the top 30 proteins list. The statistical literature shows that ranking methods accounting for uncertainty by optimizing a loss function outperform other methods of ranking, (Shen and Louis, 1998; Lin and others , 2006; Henderson and Newton, 2016) therefore ranks for the malaria and lung cancer studies obtained by using the Bayseian model outputs are preferable to those obtained using other estimates of normalized fluorescent intensity (Bérubé and others , 2022).…”
Section: Resultsmentioning
confidence: 99%